Walk the talk: bringing spirituality to workplace through transformational leadership and emotional intelligence in higher education institutions - Nauman Majeed,; Samia Jamshed,; Mohammad Nazri,; Norizah Mohd Mustamil, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Leadership stayed at the pinnacle in the arena of organizational behavior research since decades and attained significant consideration of scholars pursuing to define multifaceted dynamics of leadership and their influence on spirit at work. Studying workplace spirituality in academicians has a high value that definitely requires attention. This study attempts to explore association amongst transformational leadership and workplace spirituality of academicians through the lens of emotional intelligence in public sector universities of Pakistan. In this study, the hypothesized model was measured by using Structural Equation Modelling – Partial Least Squares. The response from 252 academicians specified that link between transformational leadership and workplace spirituality is statistically noteworthy where emotional intelligence plays a significant role as mediator. The findings enhance positive effects of transformational leadership style consistent with workplace spirituality contributing significantly to leadership literature in the higher education sector and suggest that institutions may implement practices that help in building the environment of workplace spirituality.